Letter (copy) - Tewson, Vincent
038-0078-001 Secretary's. HVT/FC/680. 295/12 H. 29th July, 1939. The Lord Mayor's Secretary, The Lord Mayor's Parlour, Council House, BIRMINGHAM. Dear Sir, Many thanks for your letter of the 28th instant. I shall be glad if you will inform the Lord Mayor of the appreciation of myself and the Basque Children's Committee for his offer to do what he can to secure help for the Walsall Home. I am sure the surplus stores which have been sent along to Walsall must have been a great help. I will pass your letter to the Secretary of the Basque Children's Committee for information. Yours sincerely, Assistant Secretary. 292/946/38/78